Giustizia digitale e forme di vita. Alcune riflessioni sul nostro nuovo mondo - Andronico, Alberto (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
Digital is not (only) an extraordinary tool in our hands, but (also, and perhaps above all) the water in which we find ourselves swimming today, sometimes without knowing it. In short, it is a language. And as such it brings with it a way of shaping our life, our thoughts and the world around us. In this context, and starting from this conviction, the text intends to focus attention on the so-called “Predictive justice”, articulating the suspicion that this expression carries with it an insidious misunderstanding, or rather two. The first is that it is still a form of justice. The second is that it really has something to do with the future.